Spatial Orientation in Cardiac Ultrasound Images Using Mixed Reality: Design and Evaluation - Maddali , Dharani; Brun, Henrik; Kiss, Gabriel; Hjelmervik, Jon Mikkelsen; Elle, Ole Jakob (Frontiers in Virtual Reality, 2022)
Spatial orientation is an important skill in structural cardiac imaging. Until recently, 3D cardiac ultrasound has been visualized on a flat screen using volume rendering. Mixed reality devices provide enhanced depth perception, spatial awareness, interaction and integration in the physical world which can prove advantageous with 3D cardiac ultrasound images. In this work, we describe the design of a system for rendering 4D (3D + time) cardiac ultrasound data as virtual objects and evaluate it for ease of spatial orientation by comparing it with a standard clinical viewing platform in a user study. The user study required 8 participants to do timed tasks and rate their experience. The results showed that virtual objects in mixed reality provided easier spatial orientation and morphological understanding despite lower perceived image quality. Participants familiar with mixed reality were quicker to orient in the tasks. This suggests that familiarity with the environment plays an important role and with improved image quality and increased use, mixed reality applications may perform better than conventional 3D echocardiography viewing systems.